Time-Based Effects of Xanthium strumarium Extract on Rats - Keeeci, Hakan; Ozturk, Yasin; Dortbudak, M. Bahaeddin; Yakut, Seda; Dagoglu, Gurdal; Ozturk, Merve (Zoological Soc Pakistan, 2022)
This study is aimed to determine the toxicity of Xanthium strumarium L. (cocklebur) or its seeds to human or an animal. Cocklebur, potentially toxic plants is found abundantly in meadows and pastures. One of the most significant ingredients that causes toxicity is atractyloside (ATR). In this study, the concentration of ATR in cocklebur seeds was determined as 4 mg/g seed. The study involved 54 rats which were divided into a total of 9 groups including one control group. A single dose of cocklebur seed extract was provided by gavage after being concentrated by 2 ml for each animal (80 mg ATR/kg) except for those in the control group, and time-dependent hepatotoxic, nephrotoxic, hematological and biochemical effects were analyzed. No histopathological change was detected in the liver and kidney tissues of the rats in the experimental groups. Both hematological and serum biochemical values (Ca, P, TBIL, ALT, AST, ALP, Urea, and Creatinine) were within the physiological limits in all groups. Consequently, in light of the obtained data, it was observed that the rats were not exposed to any toxic effect even when they consumed a stomach full of cocklebur fruit at once.
Keywords: Cocklebur; Xanthium strumarium; Atractyloside; Toxication; Hepatotoxicity; Nephrotoxicity